2009
DOI: 10.1007/s11248-009-9255-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of gene flow from a herbicide-resistant indica rice (Oryza sativa L.) to the Costa Rican weedy rice (Oryza sativa) in Tropical America: factors affecting hybridization rates and characterization of F1 hybrids

Abstract: Herbicide-resistant rice cultivars allow selective weed control. A glufosinate indica rice has been developed locally. However, there is concern about weedy rice becoming herbicide resistant through gene flow. Therefore, assessment of gene flow from indica rice cultivars to weedy rice is crucial in Tropical America. A field trial mimicking crop-weed growing patterns was established to assess the rate of hybridization between a Costa Rican glufosinate-resistant rice line (PPT-R) and 58 weedy rice accessions bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…Biological factors may have played an essential role in determining outcrossing rates among weedy rice populations, although environmental conditions, such as air temperature, strength and direction of wind, and air humidity, could also considerably affect outcrossing rates. Previous studies indicated variable frequencies of gene flow from cultivated rice to diverse groups of weedy rice with different genetic backgrounds [20], [30], [31], [48], which is in a good accordance with data of outcrossing rates in this study. Our findings demonstrate that it is relatively easy for weedy rice to receive pollen from its sexually compatible rice cultivars (including GM rice) occurring at the close vicinity.…”
Section: Discussionsupporting
confidence: 92%
“…Biological factors may have played an essential role in determining outcrossing rates among weedy rice populations, although environmental conditions, such as air temperature, strength and direction of wind, and air humidity, could also considerably affect outcrossing rates. Previous studies indicated variable frequencies of gene flow from cultivated rice to diverse groups of weedy rice with different genetic backgrounds [20], [30], [31], [48], which is in a good accordance with data of outcrossing rates in this study. Our findings demonstrate that it is relatively easy for weedy rice to receive pollen from its sexually compatible rice cultivars (including GM rice) occurring at the close vicinity.…”
Section: Discussionsupporting
confidence: 92%
“…However, even in the absence of such an advantageous environment, heterosis might play an important role that enhances the phenotypic performance of those transgenic hybrids (Oard et al 1996). The success of heterotic hybrids may also vary widely depending on taxa and genotypes (Ellstrand 2003), environments and seasons , and phenotypic traits (Oard et al 2000;Zhang et al 2003Zhang et al , 2008Cao et al 2009;Sanchez Olguin et al 2009). Some traits may lead to better performance and vigor compared with parental lines, while others exhibit a mid-parent level or even decreased performance.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that GM rice may hybridize with traditional cultivars (Messeguer et al 2001(Messeguer et al , 2004Rong et al 2005Rong et al , 2007Jia et al 2007;Yuan et al 2007;Yao et al 2008), weedy rice (Zhang et al 2003(Zhang et al , 2006Chen et al 2004;Messeguer et al 2004;Sanchez Olguin et al 2009), and wild rice (Chen et al 2004;Yao et al 2008). A few GM rice lines have been developed in Korea, including those tolerant to herbicides (Lee et al 2007) and abiotic stresses (Jang et al 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glufosinateresistant rice was deregulated (approved for sale) but never commercialized, perhaps partly because of the potential problem of gene flow to weedy rice and nontransgenic rice (Oard et al, 2000;Olofsdotter et al, 2000;Sanchez-Olguin et al, 2009;Song et al, 2011). The adoption of glufosinateresistant crops has been only a small fraction of the HR crop market, primarily because glyphosate is a more effective herbicide than glufosinate on many weed species.…”
Section: Herbicidementioning
confidence: 99%